Personalised haemodynamic management targeting baseline cardiac index in high-risk patients undergoing major abdominal surgery: a randomised single-centre clinical trial. (August 2020) - Nicklas, Julia Y.; Diener, Oliver; Leistenschneider, Maximilian; Sellhorn, Christina; Schön, Gerhard; Winkler, Martin; Daum, Guenter; Schwedhelm, Edzard; Schröder, Julian; Fisch, Margit; Schmalfeldt, Barbara; Izbicki, Jakob R.; et al.
Abstract: Background: Despite several clinical trials on haemodynamic therapy, the optimal intraoperative haemodynamic management for high-risk patients undergoing major abdominal surgery remains unclear. We tested the hypothesis that personalised haemodynamic management targeting each individual's baseline cardiac index at rest reduces postoperative morbidity. Methods: In this single-centre trial, 188 high-risk patients undergoing major abdominal surgery were randomised to either routine management or personalised haemodynamic management requiring clinicians to maintain personal baseline cardiac index (determined at rest preoperatively) using an algorithm that guided intraoperative i.v. fluid and/or dobutamine administration. The primary outcome was a composite of major complications (European Perioperative Clinical Outcome definitions) or death within 30 days of surgery. Secondary outcomes included postoperative morbidity (assessed by a postoperative morbidity survey), hospital length of stay, mortality within 90 days of surgery, and neurocognitive function assessed after postoperative Day 3. Results: The primary outcome occurred in 29.8% (28/94) of patients in the personalised management group, compared with 55.3% (52/94) of patients in the routine management group (relative risk: 0.54, 95% confidence interval [CI]: 0.38 to 0.77; absolute risk reduction: –25.5%, 95% CI: –39.2% to –11.9%; P <0.001). One patient assigned to the personalised management group, compared with five assigned to the routine management group, died within 30 days after surgery ( P =0.097). There were no clinically relevant differences between the two groups for secondary outcomes. Conclusions: In high-risk patients undergoing major abdominal surgery, personalised haemodynamic management reduces a composite outcome of major postoperative complications or death within 30 days after surgery compared with routine care. Clinical trial registration: NCT02834377.